Strategies for equity, diversity and inclusion in geriatric healthcare professional curricula: A scoping review protocol. - Kristina M Kokorelias; Vicky Chau; Sachindri Wijekoon; Hardeep Singh; Maurita T Harris (PLoS ONE, 2024)
Introduction The pursuit of Equity, Diversity and Inclusion (EDI) in healthcare education has garnered significant attention in recent years, reflecting a broader societal imperative for equitable healthcare delivery. However, existing curricula within geriatric healthcare education may not adequately address these diverse needs within their educational frameworks, inadvertently resulting in disparities in care delivery and outcomes. Within the realm of geriatric healthcare, addressing EDI is particularly crucial due to the diverse needs of older adult populations and the imperative for healthcare professionals to deliver culturally humble care. This review provides a comprehensive overview of strategies and curricular strategies, actions and/or initiatives to promote EDI within geriatric healthcare professional education. Methods This paper presents a protocol for a forthcoming scoping review. The methodology for this scoping review adheres to the framework outlined in the Joanna Briggs Institute (JBI) Manual, encompassing four main stages: (1) formulation of a search strategy, (2) screening and selection of evidence, (3) data extraction, and (4) analysis. We will conduct a comprehensive search of peer-reviewed and empirical literature. Additionally, we will explore the reference lists of included studies to identify any relevant sources. The synthesis of findings will be conducted through a narrative approach. Reporting of the methods and results will adhere to the guidelines provided by the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR). Discussion Healthcare professionals must possess the knowledge, skills, and attitudes necessary to deliver culturally humble care that respects and responds to diverse older adults' unique needs and preferences. The review aims to fill a crucial gap in the literature by providing a comprehensive overview of strategies and curricular interventions designed to promote EDI within geriatric healthcare professional education. By mapping these strategies, actions and/or initiatives, the review seeks to identify trends, challenges, and opportunities for advancing EDI within geriatric care. The forthcoming review serves as a call to action for educators, healthcare institutions, and decision makers to prioritize EDI within geriatric healthcare education. The review identifies effective strategies and interventions for promoting EDI, providing actionable insights to inform the development of inclusive curricula, training programs, and institutional policies, which can contribute to cultivating a healthcare workforce better equipped to address the complex and evolving needs of aging populations equitably and compassionately.